RESOR PANTAI WEDI OMBO DI GUNUNG KIDUL, YOGYAKARTA - Tri Mardiyanti; Suparno Suparno; Hari Yuliarso (ARSITEKTURA, 2016)
Design Resort on Wedi Ombo beach against the background of growth of tourists increasing every year, but a means of lodging accommodations not meet the need for accommodation for tourists, so the purpose of this scheme is to get a building design that can facilitate tourism activities, facilitate the activities of coastal tourism into a building form that apply to the tropical climate adaptation in coastal Wedi Ombo environments. Design issues are: how to apply the concept of tropical architectural design in the form of Wedi Ombo beach resort building. The method used is a method of planning and architectural design ranging from the initial idea and understanding of the object that  planned, the formulation of the problem, the collection of physical and potential data area which is then analyzed and examined to obtain the results of the application of the concept of tropical architecture of the building. The result obtained is a design of a resort, which can optimize the potential of the nature of tropical climate on the design of the building, so there is a sense of comfort for the users of the building at the time were in the building.